COMMUNICATION MODELS EMPLOYED BY ISLAMIC RELIGIOUS EDUCATION TEACHERS IN THE MORAL DEVELOPMENT OF STUDENTS AT SMAIT AL FITYAH PEKANBARU - Muhammad Raihan Ramadhan; Devi Arisanti; Artis (STAI Nusantara Kota Banda Aceh, 2026)
This study aims to examine the communication models employed by Islamic Religious Education teachers in the moral development of students at SMAIT Al Fityah Pekanbaru and to identify the factors influencing their implementation. The study used a qualitative approach with a descriptive method. The primary informants were Islamic Religious Education teachers, while the supporting informants included the principal and the vice principal for student affairs. Data were collected through interviews, observations, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing. Communication models play a significant role in moral education because they enable teachers to establish personal relationships with students, understand their characteristics, and become moral role models within the educational environment. The findings indicate that Islamic Religious Education teachers applied three major communication models in fostering students’ morality: linear, interactive, and transactional communication models. The linear communication model was implemented through lectures and moral advice delivered directly to students. The interactive communication model was reflected in question-and-answer sessions, discussions, and the provision of rewards to encourage students’ participation and motivation in the learning process. Meanwhile, the transactional communication model involved collaboration among Islamic Religious Education teachers, homeroom teachers, student affairs staff, other teachers, and parents in supporting students’ moral development. The study concludes that effective moral development requires not only instructional competence but also effective communication patterns involving cooperation between teachers, schools, and parents to create a supportive moral educational environment.